Relaxation and Oscillation Model Using Caputo Fractional Differential Equations - Ardan, Wildy; Fatimah, Siti; Yulianti, Kartika (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2023)
The phenomenon of relaxation and oscillation is a common event that is often encountered. Both of these properties can occur in viscoelastic materials even though they do not occur simultaneously. Because the characteristics of viscoelastic materials are difficult to describe using classical-order differential equations, in this study, fractional-order differential equations were used to model each of the relaxation and oscillation phenomena in viscoelastic materials with the help of Laplace transform as a solution method . The solution obtained characterizes the phenomenon of memory effect as well as viscoelastic materials in general. In addition to this phenomenon, several other variables were also found to be the influence of the related material motion dynamics.